ANALISIS MATERI DALAM APLIKASI DEUTSCH H?REN & LESEN SEBAGAI MEDIA PEMBELAJARAN BAHASA JERMAN KELAS X - Ningrum, Widya Putri; Pujosusanto, Ari (LATERNE, 2022)
This study uses a qualitative method with literature study which aims to describe the results of content analysis in the Deutsch H?ren & Lesen application as a means of learning German for class X. The data is extracted from the Deutsch H?ren & Lesen application based on Android games containing material A1 to B2. with different themes in the form of questions and audio. The data used is A1 material with 14 themes. However, the Deutsch H?ren & Lesen application needs to be adapted to the 2013 Curriculum to be used as a learning reference according to the learning criteria in Indonesian media and education. Therefore, this article takes the formulation of the problem whether the German language material in the Deutsch H?ren & Lesen application is in accordance with the listening skills of class X semester 1. The data obtained is then analyzed, the analytical technique used is content analysis or content analysis using learning media theory, material suitability theory, audio teaching material theory and 2013 Curriculum. The results of the analysis explain in detail that the application of Deutsch H?ren & Lesen to the topics of Ich bin Tom, Struppi, Marie und Ihre Familie is very much in accordance with the 2013 Curriculum and has a percentage score of 96% and media selection criteria has a percentage score of 91%.